Social exclusion, criminal policy and criminal responsibility in Peru: a reinterpretation of article 15 of the criminal code - Chanjan Documet, Rafael (2025)
The permanent situation of social exclusion experienced by some people in Peru requires that the criminal system give them special treatment for certain criminal acts in order to implement a criminal policy in accordance with a Social and Democratic State of Law. This paper critically analyzes the current Peruvian criminal policy model, which has a punitive or “soft hand” treatment depending the type of crime, and which tends to perpetuate and aggravate the situation of social exclusion of some groups, not significantly reducing crime rates. Therefore, a reflection is proposed on the dogmatic category of culpability, specifically exigibility, in order to exonerate or reduce the criminal responsibility of these people for certain types of crimes, reinterpreting article 15 of the Peruvian Criminal Code.